2015
DOI: 10.1155/2015/742914
|View full text |Cite
|
Sign up to set email alerts
|

Moxibustion Reduces Ovarian Granulosa Cell Apoptosis Associated with Perimenopause in a Natural Aging Rat Model

Abstract: In recent years, concerns about the adverse effects of hormone replacement therapy have increased interest in alternative therapies for the management of the symptoms of perimenopause. Here, we investigated the effects of moxibustion, a traditional Chinese practice that is involved in heated Artemisia vulgaris (mugwort) stimulation, on hormonal imbalance and ovarian granulosa cell (GC) apoptosis in a rat model of perimenopause. Our results showed that mild warm moxibustion (MWM) modulated the circulating level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Moxibustion has also exhibited antiaging effects, protection of neuronal structure, and reduction in the rate of neural degeneration [9]. Previously, this team has studied the effects of moxibustion on ovarian granulosa cell apoptosis in aging rats, elucidating a mechanism for improving perimenopausal syndrome in female rats by [10]. To date, few studies have addressed whether moxibustion can improve testicular function and its underlying mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Moxibustion has also exhibited antiaging effects, protection of neuronal structure, and reduction in the rate of neural degeneration [9]. Previously, this team has studied the effects of moxibustion on ovarian granulosa cell apoptosis in aging rats, elucidating a mechanism for improving perimenopausal syndrome in female rats by [10]. To date, few studies have addressed whether moxibustion can improve testicular function and its underlying mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…It uses Folium Artemisiae argyi to produce moxibustion materials, generating heat upon combustion to stimulate acupoints or specific body surface sites, thereby achieving disease prevention and treatment. Increasing evidence has demonstrated that moxibustion is able to improve ovarian function (8)(9)(10)(11)(12). It has been reported that the early use of moxibustion is able to generate a favorable stress response to resist or reduce the subsequent disease and delay the degradation of normal tissues (13).…”
Section: Introductionmentioning
confidence: 99%
“…Acupuncture and moxibustion therapy have demonstrated to be potential treatments for a variety of sex hormone-related diseases, such as premature ovarian failure and perimenopausal syndrome, [39][40][41][42] as they can improve levels of oestrogen (estradiol, progesterone and prolactin) 40 Moxibustion has been shown to regulate circulating levels of estradiol and follicle-stimulating hormone in the ovaries of perimenopausal rats as well as to inhibit ovarian granulosa cell apoptosis through the Forkhead box Protein O1 and JAK2/STAT3 pathway, similar to exogenous oestrogen supplementation. 41 Moxibustion also improves the antioxidant stress-related genes HO-1 and NQO-1 and their protein levels, and enhances antioxidant capacity. 43 44 In addition, moxibustion has anti-inflammatory potential, resulting in local or systematical reduction of IL-2, IL-6 and TNF-α levels, 45 46 for the treatment of ulcerative colitis, lumbar disc herniation, periarthritis of shoulder and fatigue.…”
Section: Discussionmentioning
confidence: 99%